Cover Feature: N‐Heterocyclic Carbene–Phosphinidene Adducts: Synthesis, Properties, and Applications (Eur. J. Inorg. Chem. 24/2018). Issue 24 (13th June 2018) - Krachko, Tetiana; Slootweg, J. Chris
Abstract : The Cover Feature shows the key aspects of the chemistry of carbene–phosphinidene adducts described in the review; namely, the synthesis of NHC=PR adducts, the structure of one of the smallest representatives, and their main types of reactivity. These compounds can be prepared by combining various carbenes with multiple phosphorus sources (e.g., cyclopolyphosphines, chlorophosphines, sodium phosphaethynolate, phosphine gas). The main types of reactions of these adducts are: addition, substitution at the phosphorus atom, and phosphinidene transfer resulting in C–P bond cleavage. More information can be found in theMicroreview by T. Krachko and J. C. Slootweg .